Effect of green hybrid fillers loading on mechanical and thermal properties of vinyl ester composites. Issue 11 (29th August 2022) - Nagaprasad, N.; Vignesh, V.; Karthik Babu, N. B.; Manimaran, P.; Stalin, B.; Ramaswamy, Krishnaraj
Abstract: The need for eco‐friendly materials has been attracted due to renewability, abundance availability, low cost, and so on. Therefore, the search for bio fillers for the fabrication of bio‐based composite materials is gaining more and more attention in both academic and industry circles because it promotes sustainability. The present study represents the utilization of biomass solid waste in the hybrid form of Tamarind Seed and Date Seed Filler (TSF/DSF) into polymer reinforced composite which has been explored for the first time by a compression molding technique. These fillers are bio‐waste that can be obtained at a minimal cost from renewable sources. An attempt has been made to use these hybrid fillers to reinforce the matrix ranging from 0 to 50 wt%, and their physical, mechanical, and thermal properties were investigated. In general, the inclusion of hybrid fillers increases mechanical properties, although the addition of hybrid fillers had only a minor impact on thermal properties. When compared to the pure vinyl ester resin, the hybrid fillers reinforced composites revealed a significant enhancement in tensile, flexural, impact, and hardness properties, with improvements of 1.51 times, 1.44 times, 1.87 times, and 1.46 times respectively, at 10 wt% filler loading. Filler matrix interaction of fractured mechanical testing samples was evaluated by scanning electron microscope. Based on the findings, hybrid filler reinforced composites may be suitable for applications where cost is a consideration and where minor compromises in thermal qualities are acceptable. Abstract : Stages of TSF/DSF filled vinyl ester composites.